2015
DOI: 10.6000/1927-5129.2015.11.60
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant and Antimicrobial Activities of Mondia whitei (Hook. f.) Skeels

Abstract: Mondia whitei (Periplocaceae)is an aromatic plant used as aphrodisiac and for the treatment of urinary infection, jaundice, headache and diarrhoea in Nigeria. The plant was screened for phytochemical components using standard techniques. The antioxidant and antimicrobial activities of the plant were evaluated. The free radical scavenging activity was determined by 2, 2-diphenyl-1-picryl hydrazyl (DPPH) assay. The antimicrobial activity of M. whitei extracts against nine clinical isolates was determined by agar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…However, the present study shows that the antimicrobial effect of the root oil against organisms conforms to previous reports on the anti-infective potential of the extracts of the plant (Gbadamosi and Erinoso, 2015;Okitoi et al, 2007;Fankam et al, 2011). When compared with the findings of Gbadamosi and Erinoso (2015), the antimicrobial (Neugebauer, 1993;Gbadamosi and Oyedele, 2012).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…However, the present study shows that the antimicrobial effect of the root oil against organisms conforms to previous reports on the anti-infective potential of the extracts of the plant (Gbadamosi and Erinoso, 2015;Okitoi et al, 2007;Fankam et al, 2011). When compared with the findings of Gbadamosi and Erinoso (2015), the antimicrobial (Neugebauer, 1993;Gbadamosi and Oyedele, 2012).…”
Section: Resultssupporting
confidence: 92%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License been earlier reported (Gbadamosi and Erinoso, 2015). Although, the aromatic roots of the plant are extensively used in tropical Africa for therapeutic purposes, there is a dearth of information on its active compounds and bioactivities of such compounds.…”
Section: Introductionmentioning
confidence: 66%
“…The study evaluated the antibacterial activity of the PE against Streptococcus mutans and result obtained are in agreement with studies conducted by [9,12,13]. Lemon extracts and MCERBE exhibited potent inhibitory activity against a broad range of both gram positive and gram negative bacteria [9,12,13].…”
Section: Discussionsupporting
confidence: 79%
“…Earlier studies revealed that citrus lemon juice possesses potent antimicrobial activity and eating fresh lemon fruits in addition to taking their juice has been associated with overall gum health and protection from dental caries [9][10][11]. Mondia whitei is an aromatic softwood climber with pale greenish-white or cream owers and its roots have a vanilla-like scent [12]. Previous studies demonstrated that the Mondia whitei crude ethanolic root bark extract (MCERBE) is effective against several oral Streptococci like S. pyogenes, S. sobrinus, and S. mitis [13].…”
Section: Introductionmentioning
confidence: 99%
“…The NO may thereafter affect the neurotransmitter activity across the brain system, which may ultimately result in a decrease in total sperm output ( 26 ). As part of its cytoprotective effect, previous works have shown that extracts of Mondia whitei have antioxidant properties ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%